Platelet Activating Factor Contributes to Vascular Leak in Acute Dengue Infection - Jeewandara, Chandima; Gomes, Laksiri; Wickramasinghe, N.; Gutowska-Owsiak, Danuta; Waithe, Dominic; Paranavitane, S. A.; Shyamali, N. L. A.; Ogg, Graham S.; Malavige, Gathsaurie Neelika (PLOS Neglected Tropical Diseases, 2015)
Author Summary Although plasma leakage is the hallmark of severe dengue infections, the factors that cause increased vascular permeability have not been identified. As platelet activating factor (PAF) is associated with an increase in vascular permeability in other diseases, we set out to investigate its role in acute dengue infection. In this study, we found that PAF was significantly increased in patients with DHF, and the PAF levels rose just before the onset of the critical phase of dengue, during which vascular leak is thought to occur. PAF in serum of dengue patients was associated with reduced expression of tight junction proteins (ZO-1) and reduction in trans-endothelial resistance (TEER) of human endothelial cells. Use of PAFR blockers significantly reduced the down regulation of ZO-1 by serum of dengue patients and also the reduction of TEER, suggesting that PAF plays a significant role in inducing vascular leak in acute dengue infections.